THE RELATIONSHIP BETWEEN SOCIAL MEDIA EXPOSURE AND ELEVENTH-GRADE STUDENTS’ WRITING ACHIEVEMENT IN EXPLANATION TEXT WRITING - Karisma Kurniawati (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
Social media is increasingly shaping students' learning behavior, including how they interact and produce written texts. However, empirical evidence regarding its specific impact on explanatory text writing remains limited. The aims of this study are to investigate and find out the effect of social media exposure to male and female students and the relationship between the social media exposure and the students’ writing achievement in explanation text writing. Thus, the research design used by the researcher was correlational research. The subjects of this study were 30 students in eleven grades that were randomly taken from two different classes at one of the public senior high schools in Gresik. Close-ended questionnaires about social media exposure were distributed and students’ explanation text writing scores were collected to obtain the data. The collected data were calculated and analyzed using an independent sample t-test and Pearson-Product Moment Correlation in SPSS. The researcher then reported the analyzed data using mean, standard deviation, t value, and Pearson r. The results showed that male and female students were not significantly different based on their social media exposure. Moreover, there was a significant but negative and weak relationship between social media exposure and Students' Writing Achievement in an explanation text writing. These results suggest that social media exposure does not excellently contribute to students’ writing results.